Moving Advertisements Systematically Affect Gaze Behavior and Performance in the Soccer Penalty Kick - Paterson, Gareth; Kamp, John van der; Savelsbergh, Geert (Frontiers in Sports and Active Living, 2020)
The aim of the current study was to investigate whether a moving advertisement positioned behind the goal area would influence the visual attention of participants performing a soccer penalty kick, and, whether this would an effect on subsequent motor performance. It was hypothesized that if the disruption would be a-specific, it would result in a decrease in penalty performance measures, especially in terms of aiming location and consistency. Alternatively, if the disruption would be specific, expected systematic changes in penalty performance and aiming which would depend on the direction of motion of the advertisement in line with the Dunker illusion. To this end, we investigated the gaze behaviour and kicking performance of intermediate skilled soccer players taking penalty kicks in three differing advertisement conditions, namely no advertisement, a stationary advertisement, and a moving advertisement. The latter condition consisted of an advertisement moving from left to right and an advertisement moving from right to left. Results showed that a moving advertisement placed behind the goal area indeed caught the visual attention of soccer penalty kickers using a goalkeeper-dependent kicking strategy, however, found no measurable distractive a-specific effects on penalty kick performance measures. However, systematic effects on aiming were found when comparing conditions in which the advertisement moved in opposite directions suggesting that the accuracy of the penalty kick is impacted by task-irrelevant contextual information in line with the Duncker illusion, suggestion that the accuracy of the penalty kick is impacted by task-irrelevant contextual information.